Developing “Double-Qualified” Teachers in Vocational Colleges: The Role of School-Enterprise Cooperation - Sun, Le (Journal of Educational Research and Policies, 2026)
As vocational education transitions from scale expansion to connotative development, the professional development of “double-qualified” teachers—those possessing both theoretical expertise and practical industry competencies—has emerged as a key research focus. This paper conceptualizes the professional development of double-qualified teachers as encompassing both the individual growth of vocational educators and the collective construction of a double-qualified teacher team. Within the framework of school-enterprise cooperation, the study proposes a shift from the traditional, school-dominated, one-way static cultivation model to a collaborative, two-way flow model. Specifically, schools and enterprises jointly improve the vocational teacher training system by strengthening both the professional knowledge and practical skills of individual teachers, thereby facilitating their development into double-qualified practitioners. Concurrently, schools and enterprises collaborate to establish a classified management and incentive mechanism for the double-qualified teacher team, providing institutional support for the professional advancement of the vocational teaching workforce, optimizing the structural composition of the double-qualified team, and ultimately enhancing the overall quality of talent cultivation in vocational education.